BREAST RECONSTRUCTION AFTER MASTECTOMY: A SURGERY FOR SELF-ESTEEM AND REBIRTH - Pedro do Valle Varela, João; Paes de Moura, Jennifer; Freire Andrade, Rodney; Monfradini da Silva, Jacqueline; Tofano Monteiro, Shayra; Zanotti Duccini, Felipe; Dalgobbo Samorini, Tullio; Hugo Mendes da Cunha, Vitor; Siqueira Dyna, Mariana; Salvador, Milena; Rodrigues de Almeida, Letícia; Pinheiro de Mello Canabarro, Davi; et al. (Health and Society, 2025)
Mastectomy, although vital in the treatment of breast cancer, can have a significant impact on patients’ self-esteem and quality of life. Breast reconstruction plays a central role in physical and emotional recovery and is widely recognized as a surgery that goes beyond aesthetics, representing a symbol of rebirth and recovery of female identity. The aim of this study is to explore the advances and benefits of post-mastectomy breast reconstruction, addressing its psychological implications, available techniques and the challenges faced by patients in the rehabilitation process. This literature review analyzes advances in breast reconstruction after mastectomy, with a focus on patient-centered outcomes, psychological implications, technological innovations and challenges in resource-limited settings. The review covers reconstruction techniques such as the use of DIEP flaps and implants, as well as exploring barriers to access and the future prospects of the field. Breast reconstruction techniques include the use of prostheses, autologous flaps and hybrid approaches, which are chosen according to the patient’s clinical conditions and preferences. Studies show that reconstruction has a positive impact on mental health, reducing rates of depression and anxiety. However, challenges such as unequal access to the procedure and fears about complications are still barriers faced. In addition, advances in biomaterials and microsurgery have improved aesthetic and functional results, increasing patient satisfaction. Therefore, breast reconstruction is more than a surgical intervention; it is a process of physical and emotional transformation that contributes to giving new meaning to the cancer experience. Investing in policies that increase access to this surgery and in technological advances that optimize the results is essential to guarantee complete and humanized rehabilitation.